Interim Results From the Partnership for Advancement in Neuromodulation Pain Registry. Issue 7 (14th February 2014) - Deer, Timothy; Skaribas, Ioannis; Nelson, Christopher; Tracy, Jerry; Meloy, Stuart; Darnule, Amit; Salmon, John; Pahapill, Peter A.; McJunkin, Tory; Sanapati, Mahendra; Lininger, Todd E.; Russo, Marc; et al.
<x xml:space="preserve">Abstract</x> Objectives The objective of this study was to present results from a multicenter registry designed to obtain longitudinal clinical outcome data for patients implanted with a neuromodulation system for the management of chronic pain of the trunk and/or limbs. Materials and Methods Interim data from 579 patients across 40 study sites were analyzed from a prospective, observational, noninterventional registry. Institutional review board approval was obtained prior to enrollment. The following were recorded at baseline and at 3, 6, and 12 months postimplant: patient‐reported pain relief, categorical ratings of pain relief, Pain Disability Index (PDI) scores, quality of life, medication usage, and patient satisfaction. Pain relief among (tobacco) smokers was also assessed. Descriptive statistics were compiled for all patient outcome measurements, and data are reported as mean (±standard deviation). All statistical analysis was conducted using one‐sided t‐tests with a significance level of α = 0.05. Device‐related adverse events were captured and are reported. Results Patient‐reported pain relief was 58.0% (±26.2%) at 3 months, 58.1% (±28.7%) at 6 months, and 57.0% (±29.4%) at 12 months. Mean PDI scores were reduced from 47.7 points at baseline to 33.3, 32.4, and 31.9 points, respectively (p ≤ 0.001). The majority of patients categorized their pain relief as "excellent" or "good" and reported their overall quality of life as "greatly improved" or "improved" at all time points. In addition, greater than 79% of patients were "satisfied" or "very satisfied" with the therapy at all time points assessed, and 47.1% of patients "stopped" or "decreased" use of narcotics/opioids. Pain relief was significantly attenuated by smoking (p = 0.042). The most common adverse event was persistent pain and/or numbness at implantable pulse generator/lead site, which accounted for 18.6% of all events in 3.2% of all patients. Conclusions These results provide evidence to further support the safety, efficacy, and sustainability of neuromodulation in clinical practice.